Preparation and Characterization of a Hydrophilic Polysulfone Membrane Using Graphene Oxide - Hoan Thi Vuong Nguyen; Thu Hong Anh Ngo; Khai Dinh Do; Minh Ngoc Nguyen; Nu Thi To Dang; Tham Thi Hong Nguyen; Vo Vien; Tuan Anh Vu (Journal of Chemistry)
In general, the polysulfone (PSf) membranes are popular choices for water treatment because they have high thermal stability and good chemical resistance. On the other hand, the filtration capacity of the polysulfone membrane is limited because of its low water flux and poor antifouling ability, which are caused by the low surface hydrophilicity of the membranes. In this research, blending of graphene oxide (GO) or graphene oxide-titanium dioxide (GO-TiO2) mixture into the polysulfone matrix had been carried out through the phase inversion method to enhance the hydrophilic and antifouling properties. Methods such as energy-dispersive X-ray spectroscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, and water contact angle measurement were used to examine the surface properties of the prepared membranes. Experimental results have led to a conclusion that graphene oxide can be stabilized into prepared membranes, and then, by reducing the water contact angle values, the surface of these membranes becomes hydrophilic, which increases the permeability and the water flux of methylene blue from the aqueous feed solution, improving the membrane’s antifouling resistance.